EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN ROUND CLUB TERHADAP HASIL BELAJAR IPA DI KELAS VI SD NEGERI ARONGAN WOYLA KECAMATAN ARONGAN LAMBALEK - Julissasman; Rita Oktavia; Dara Magfirah (Jurnal Bionatural, 2025)
The aim of this research is to determine the effectiveness of the Round Club learning model on the science learning outcomes of class VI students at SD Negeri Arongan Woyla, Arongan Lambalek District. The type of research used is quantitative descriptive research using a quantitative approach. The research subjects were class VI students at SD Negeri Arongan Woyla, Arongan Lambalek District with a total of 14 students consisting of 7 boys and 7 girls. The data collection techniques used are tests, observation and documentation. The data analysis technique used is a descriptive percentage analysis technique. Based on the research results, it shows that the percentage of student learning completion after implementing the Round Club learning model was 93% or 13 students who had completed it, while only 1 student or 7% had not completed it with the average student score obtained being 81.78. Thus, it can be concluded that the implementation of the Round Club learning model is effective on science learning outcomes, especially on the theme of saving creatures in class VI of SD Negeri Arongan Woyla, Arongan Woyla District.